DEPOSITIONAL ENVIROMENT CARBONATES SANDSTONE UNIT OF THE NYALINDUNG FORMATION BASED ON OUTCROP DATA - Firmansyah, Yusi; Ganjar Gani, Reza Mohammad; Fachrudin, Kurnia Arfiansyah (Faculty of Geological Engineering, Universitas Padjadjaran, 2017)
The research area is located in Loji Village, Simpenan District, Sukabumi Regency, West Java Province. The research was conducted by geological mapping method. The determination of the carbonaceous rocks precipitation environment based on the characteristics of lithology and fossil analysis. Based on the characteristics of lithology, this unit consists of carbonate sandstones. In megaskopis unit of this Carbonate Sandstone has physical characteristics, brown, medium grain sand size - very fine sand, circular round, open pack - closed, good sorting and bad permeability. The results of fossil foraminifera bentonic and plantonic analysis show that the bathymetry zone is at the outer center of neritik So it can be predicted that the deposition environment of this unit is in shallow sea.Keywords : lithologic characteristics, bentonic foraminifera, depositional environment